VALU 2014 - SVT exit poll survey parliamentary election 2014 - Holmberg, Sören; Näsman, Per; Gustafsson, Torbjörn (Sveriges Television, 2015)
This exit poll survey was carried out in connection with the parliamentary election on September 14, 2014.

In VALU - Swedish exit poll surveys - voters leaving polling stations are asked by public service broadcaster Sveriges Television (SVT) to fill in a questionnaire and put it anonymously in a sealed box. After collecting and processing the responses, Sveriges Television is able to present an election forecast and an analysis of the reasons underlying the outcome of the election in it´s Election Night broadcast. The surveys are referred to as VALU, an abbreviation for vallokalsundersökning, Swedish for exit poll survey. The first exit poll survey in Sweden was carried out at the parliamentary election in 1991. Since then similar studies have been carried out in connection with all Parliamentary elections, referendums and elections to the European Parliament.

Purpose:

Provide analytical support for the election night broadcast on Swedish television during the election night, and for other post-election analysis.

Denna vallokalsundersökning genomfördes i anslutning till riksdagsvalet den 14 september 2014.

En vallokalsundersökning (exit poll) innebär att man frågar ett urval av väljare då de lämnar vallokalen dels vilket parti de röstat på och dels ett antal valsociologiska frågor. Undersökningsmetoden har med framgång använts i ett flertal länder för prognos- och analysändamål. Den första vallokalsundersökningen i Sverige genomfördes vid riksdagsvalet 1991. Liknande undersökningar har sedan dess genomförts i samband med samtliga riksdagsval, folkomröstningar och val till Europaparlamentet.

Syfte:

Ge ett analysunderlag för den valvaka som sändes i Sveriges Television under valkvällen, samt för andra eftervalsanalyser.
VALU 2014 - SVT:s vallokalsundersökning riksdagsvalet 2014
VALU14
Keywords: local government elections; kommunalval; religious attendance; religiöst deltagande; trust; förtroende; exit polls; vallokalsundersökningar; voting; röstning; parliamentary elections; riksdagsval; voting behaviour; väljarbeteende; election data; valdata; government; regering; political parties; politiska partier; political leaders; politiska ledare; electoral issues; valfrågor; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap